Factors affecting sanitation coverage in three income levels and potential toward achieving SDG 6.2 - Bankole, Abayomi Oluwatobiloba [UNESP]; James, Abraham Olamilekan [UNESP]; Odjegba, Enovwo Erere; Bankole, Afolashade Racheal [UNESP]; Emmanuel, Babajide I. [UNESP]; Fiore, Fabiana A. [UNESP]; Pu, Jaan H.; Moruzzi, Rodrigo [UNESP] (My University, 2023)
An equitable sanitation coverage promotes sustainability, economic prosperity, and public health protection. This study examined factors affecting sanitation coverage and the potential of selected countries across three income levels (Low-Income, Lower-Middle, and Upper-Middle Income Countries) to meet Sustainable Development Goal 6.2 by developing a Sanitation Coverage Index (SCI). Nine developing countries were selected based on the following sets of criteria: income level, population, and geographical region. Twenty years (2000-2020) of sanitation coverage data were extracted from the JMP database and visualized. The SCI was developed using the service level criteria and examined the local drivers of poor sanitation coverage. Findings show that all countries studied made good progress and have commendable current status, except Ethiopia, Rwanda, and Nigeria. Nigeria has the highest open defecation coverage and may not meet the 2030 target. The SCI result shows that Turkey, Ukraine, and China have excellent coverage (scoring: 44, 43, and 40). Brazil, Bangladesh, and DPR Korea have satisfactory performances (36, 31, and 31), while Nigeria, Rwanda, and Ethiopia recorded unsatisfactory progress (28, 27, and 16). The strongest factors influencing poor coverage include population, high socioeconomic inequalities, and socio-political challenges. Therefore, the institutionalization of minimum acceptable standards, adequate sensitization, and funding could improve sanitation coverage in the countries assessed.
Keywords: Population; Public health; Sanitation coverage; Socio-political; Sustainable development